Numerical study on the effect of transverse crack self-healing on the corrosion rate of steel bar in concrete. (September 2021) - Peng, Chen; Wu, Qing; Shen, Jiao; Mo, Rui; Xu, Jun
Abstract: Reinforced concrete is subject to degradation by cracking of the concrete and corrosion of the steel reinforcing bars. This study explores the influence of transverse crack self-healing on the corrosion rate of steel bars by developing a deformed mesh model. The dynamics of transverse cracking and steel bar surface potential distributions are also explored, and parameter sensitivity analysis of the corrosion current density is conducted. The results show that steel bars have a lower surface potential at transverse cracks than in non-cracked areas, which decreases with exposure time. Crack self-healing not only reduces the corrosion rate and surface potential of steel bars but also reduces the rate of chloride-ion diffusion into concrete. Increasing the thickness of the concrete's protective layer is an effective way to slow the corrosion of steel bars. Highlights: Dynamic self-healing simulation of transverse cracks based on deformed mesh. The coupling of self-healing of cracks and electrochemical corrosion of steel bars. The effect of self-healing of cracks on the corrosion current of steel bars is ascertained.